EFFECTS OF HEAVY METAL POLLUTION ON SOIL MICROORGANISMS AND BIOCHEMICAL PROCESSES - Davis.R.P. (International Journal of Literature and Language Studies, 2026)
Heavy metal pollution is a serious environmental problem that affects soil fertility and microbial activity. Soil microorganisms play a key role in nutrient cycling, organic matter decomposition, and ecosystem stability. This study examines the effects of heavy metals on soil microbial communities and biochemical processes. The findings indicate that cadmium, lead, mercury, and chromium reduce microbial biomass, inhibit enzyme activity, and disturb nitrogen and carbon cycles.